Financial Literacy as a Solution for Bank Marketing Myopia - Robert Mesrob DerMesrobian (PT FORMOSA CENDEKIA GLOBAL, 2023)
Profit maximization through offering customer-centric products, sometimes with manipulative approaches, has been the norm for bank strategies. Therefore, some sort of bank marketing myopia rules the financial markets. Yet, these practices have been proven of being self-deteriorating. This research discusses the possibility of both banks and their clients benefiting from a higher degree of financial literacy. Banks would no longer have the need to be myopic, clients will no longer be afraid of getting scammed. A win-win situation is proposed with the use of S&P’s global financial literacy survey results and macroeconomic data from the World Bank and IMF’s databases.